Progress in nanocomposite based flexible temperature sensors: A review - Saket Sanjay Phadkule; Shrutidhara Sarma (Measurement: Sensors, 2023)
Accurate monitoring and control of localized temperature is crucial to assess health conditions, to detect and diagnose diseases early and to offer possibilities of building smart healthcare systems. Flexible temperature sensors offer conformal attachment with the human skin for stable and continuous measurements and have therefore garnered extensive attention in recent years. However, although significant achievement has been made in terms of enhancing sensitivity or gaining stability under deformation, they are still limited by low accuracy under large mechanical strain, slow response in dynamic environments, increasing hysteresis and limited measurement range. In addition, large and continuous mapping in flexible formats is required to accurately realize temporal and spatial variation of physiological temperature before such devices can be practically applied for continuous health monitoring or in electronic skin measurements. This review comprehensively presents significant advances in flexible temperature sensors based on nanocomposite materials categorizing the work according to materials, sensor design, sensing mechanisms and compatible fabrication strategies. For comparison, a few traditional temperature sensors are also reported. Finally, critical issues in the field are discussed, technical gaps are highlighted and possible solutions are suggested that may help overcome the existing challenges.